1998
DOI: 10.1002/hep.510280610
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of thrombospondin-1 and hypovascularity in human cholangiocarcinoma

Abstract: Physiological angiogenesis results from the balance of angiogenesis activators and inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 18 publications
(28 reference statements)
5
54
1
Order By: Relevance
“…On initial inspection, our results may seem contradictory to Maeda et al (4,26) because we found that the expression of TSP-1 in colorectal liver metastases was negatively prognostic. However, on closer analysis, the differences may be explained by the site of expression of TSP-1.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…On initial inspection, our results may seem contradictory to Maeda et al (4,26) because we found that the expression of TSP-1 in colorectal liver metastases was negatively prognostic. However, on closer analysis, the differences may be explained by the site of expression of TSP-1.…”
Section: Discussioncontrasting
confidence: 98%
“…Tumors with high VEGF and low TSP-1 had higher microvessel counts and by multivariate analysis worse prognosis with a 73% recurrence rate. Similarly, in hepatocellular carcinoma, high levels of TSP-1 and low levels of VEGF equated with low microvessel density (26).…”
Section: Discussionmentioning
confidence: 96%
“…A number of studies have shown a relationship between VEGF expression, or angiogenesis and p53 mutation in human tumors. Some studies showed a positive correlative relationship (25,26), but others did not (27,28). However, no study has yet examined the relationship between p53 overexpression and angiopoietin expression in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Increased VEGF expression has been reported to be associated with a significant vascularization of human intrahepatic cholangiocarcinomas, as assessed by microvessel density [135,136] . In comparison, hypovascularity of cholangiocarcinoma may be related to a downregulation of VEGF together with an up-regulation of the angiogenesis inhibitor thrombospondin-1 [136,141,142] , although further studies are needed to validate the likelihood of this being a primary mechanism underlying the limited angiogenesis observed in cases of intrahepatic cholangiocarcinoma.…”
Section: Vegfmentioning
confidence: 99%